1986
DOI: 10.1111/j.2044-8325.1986.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Management selection in Britain: A survey and critique

Abstract: The results of a survey of the techniques used for managerial selection from 108 organizations in Great Britain are presented. The results reveal that, whilst the usage by large organizations of assessment centre type exercises and biodata is increasing, most organizations still select managers on the basis of interviews and references. It is argued that psychological research and theory should have a bigger impact on selection practice. The limitations of current research and theory are discussed under the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 16 publications
12
99
1
Order By: Relevance
“…Indeed, a critique of the value of interviews for selection was made in a leading New Zealand business newspaper a year prior to our administration of the questionnaire to the experts (Penney, 1984). The conclusion that the interview is the most widely used method is consistent with the evidence summarized in Robertson and Makin (1986) and in Weekley and Gier (1987).…”
Section: Research Vs Practicesupporting
confidence: 72%
“…Indeed, a critique of the value of interviews for selection was made in a leading New Zealand business newspaper a year prior to our administration of the questionnaire to the experts (Penney, 1984). The conclusion that the interview is the most widely used method is consistent with the evidence summarized in Robertson and Makin (1986) and in Weekley and Gier (1987).…”
Section: Research Vs Practicesupporting
confidence: 72%
“…The use of different methods in some European countries is shown in Table 3. Similar results were given by Robertson and Makin (1986).…”
Section: Personnel Selectionsupporting
confidence: 79%
“…The results of these are summarized in Table 1 (note that for later comparative purposes, we also include the corresponding data from the present study in the last column of the table). Robertson and Makin (1986) found that interviews were almost universally used, followed by references. Their sample was based on just over 100 organizations from the Times 1000 index (this gives a rank order of the top 1000 UK organizations, largely based on sales).…”
Section: Surveys Of Selection Practices In the Ukmentioning
confidence: 99%
“…The survey design was informed by previous studies of the use of selection methods in organizations (Bartram et al, 1995;Heneman & Berkley, 1999;Hornsby & Kuratko, 1990;McEvoy, 1984, Robertson & Makin, 1986. The survey included three broad areas: (1) company demographics; (2) employee demographics, and (3) employee selection methods used.…”
Section: Surveymentioning
confidence: 99%